Bentyia (Kukyia): a Songhay–Mande meeting point, and a “missing link” in the archaeology of the West African diasporas of traders, warriors, praise-singers, and clerics - Paulo Fernando de Moraes Farias (Afriques)
The present tragedy in Mali draws our attention to the divisions, tensions and conflicts between West African ethnic groups, religious persuasions, and populations from different regions, in both the present and the past. But a long-term critical perspective on the past brings to light borrowings between cultures, and shows how the mobility of people across West Africa links regional and ethnic histories. The communication axis running from the Aḍagh to the Niger and, along the Niger Valley, from Gao to Busa (in Nigerian Borgu) and beyond, is a strategic locus for investigating this mobility and connectivity. It has linked together the Saharan, savannah, and forest zones of West Africa. It was a magnet for diasporas of Soninke praise-singers and Mande warriors and traders. Fishermen and other waterfolk along the river, oral traditionists and other craftspeople, priests and priestesses of African cults, and Islamic clerics, as well as armies, long-distance merchants, and enslaved human beings, moved along it. Although the archeological sites at Bentyia/Kukyia occupy a strategic position on this historical axis, they have not been excavated, whence a serious gap in our knowledge of the history of the eastern Niger Valley and of West Africa as a whole.